2002
DOI: 10.1021/cm0108583
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microhotplate Arrays as Microdeposition Substrates for Materials Exploration

Abstract: An approach for high-throughput rapid screening of chemical vapor deposition (CVD) materials using micromachined silicon microheater arrays is described. To illustrate this approach, titanium dioxide was deposited by CVD, using titanium(IV) nitrate and titanium-(IV) isopropoxide at temperatures between 130 and 815 °C. Deposition was confined to the microhotplate elements within 4-and 16-element arrays. Film microstructure was examined by scanning electron microscopy. In situ electrical measurements were made w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Tungsten trioxide, WO 3 , and bismuth vanadate, BiVO 4 , were chosen as proof-of-concept materials to demonstrate the technique on candidate photoanodes for use in a PEC device.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tungsten trioxide, WO 3 , and bismuth vanadate, BiVO 4 , were chosen as proof-of-concept materials to demonstrate the technique on candidate photoanodes for use in a PEC device.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A detailed analysis was performed to realize and verify a conformal and insulating ALD-treatment of the pores and to obtain a uniform polishing of the top surface (see ESI †). Electrochemical measurements were performed in a custom electrochemical cell that was equipped with a xed-position working electrode, a Pt mesh counter electrode, and a Ag/AgCl 4 . Control experiments veried that the stirring and/or electrode placement did not affect the measured data, due to the small currents involved and the high concentration of the electrolyte.…”
Section: -20mentioning
confidence: 99%
See 2 more Smart Citations
“…Hyett and Parkin [7] describe a crossflow reactor configuration where separate precursor inlet nozzles are used to produce films with composition gradients of tungsten and titanium oxides and to likewise generate films with varying ratios of TiO 2 rutile/anatase phases. In Taylor and Semancik [12], microhotplate devices were used to control the temperature in an array of micro-scale substrate samples; it was found that temperature gradients in the microhotplate supports resulted in a microstructurally graded film on the support legs. Finally, the Programmable Reactor system [5,6,9,10] features a segmented shower head design where each segment is fed individually with reactant gases and exhaust gas is pumped back up through each segment.…”
Section: Combinatorial Cvdmentioning
confidence: 99%